EFFORTS TO IMPROVE STUDENTS' ACADEMIC INTEGRITY THROUGH RELIGIOUS CULTURE - Muharromah, Lailil; Zubaidi, Ahmad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to uncover the impact of religious culture on the academic integrity of students at Madrasah Aliyah Darul Ulum Lumajang. Using a qualitative approach with a case study design, this research involves in-depth interviews, participatory observations, and document analysis. The research results show that religious education and a conducive learning environment play a significant role in shaping students' academic integrity. The moral values taught in religion, such as honesty and responsibility, become a strong foundation for student behavior. Additionally, the madrasah environment that emphasizes religious values creates an atmosphere that supports ethical behavior. Nevertheless, this study also found challenges such as academic pressure and the influence of the social environment that can trigger cheating behavior. This study concludes that a strong religious culture can serve as a fortress for students' academic integrity. However, continuous efforts are needed to ensure that religious values are effectively internalized and the learning environment remains conducive.